Answer:
15 years
Step-by-step explanation:
subtract 30000 from 36000 to get 6000, then subtract 2000 from 2400, you get 400, then divide 6000 by 400
Answer:
6
Step-by-step explanation:
60% of 50 is 30 and 20% of 30 is 6
X = -6/5 I hope this helps
Answer:
Solving 14t-3t we get 22 and 3t-14t we get -22
So, 14t-3t is not equivalent to 3t-14t.
Step-by-step explanation:
We need to explain weather 14t-3t is equivalent to 3t-14t. Support your sender by evaluating the expression for t=2.
<em>Equivalent expressions are those that have same values for any value of variable substituted.</em>
Now, We check if our expressions are equivalent, by evaluating the expression for t=2.
If they are equivalent, they would have same result after evaluation.
First, put t=2 into 14t-3t
![14t-3t\\Put\:t=2\\=14(2)-3(2)\\=28-6\\=22](https://tex.z-dn.net/?f=14t-3t%5C%5CPut%5C%3At%3D2%5C%5C%3D14%282%29-3%282%29%5C%5C%3D28-6%5C%5C%3D22)
Now put t=2, into 3t-14t
![3t-14t\\Put\:t=2\\=3(2)-14(2)\\=6-28\\=-22\\](https://tex.z-dn.net/?f=3t-14t%5C%5CPut%5C%3At%3D2%5C%5C%3D3%282%29-14%282%29%5C%5C%3D6-28%5C%5C%3D-22%5C%5C)
For solving 14t-3t we get 22 and 3t-14t we get -22
So, 14t-3t is not equivalent to 3t-14t.
Pythagorean Theorem: a^2 + b^2 = c^2
a = 6
c = 9
b = ?
6^2 + b^2 = 9^2
36 + b^2 = 81
b^2 = 81 - 36
b^2 = 45
b = sqrt(45)
b = 6.71 miles